Associação entre rastreamento positivo para insegurança alimentar e menor comprimento de telômeros em pessoas idosas - Polo, Celi Macedo (2024)
Brazil has a growing proportion of older people, a population that is susceptible to food insecurity due to its economic and physiological vulnerability. Food insecurity in the older people is related to economic and health issues, and may be the cause of many non-transmissible chronic conditions and even the worsening quality of aging. Telomere length is considered a biomarker and is related to cellular aging, shortening with advancing age, in addition to being associated with several diseases linked to aging. Telomere length is considered a senescence biomarker and is related to cellular aging, shortening with advancing age, in addition to being associated with several diseases linked to aging. The objective of this study is analyze related individual characteristics of older people with food insecurity and to verify the association between food insecurity and shorter telomere length. This is a cross-sectional study in which socioeconomic, health, food insecurity and telomere length data were obtained from a sample of 440 older people residing in the urban area of the municipality of Alfenas/MG. Data collection was carried out in two stages: personal interview and blood collection. The blood sample was used for the relative quantification of telomere length using real-time qPCR, that were categorized into quartiles. Food insecurity was verified using the short version of the Brazilian Food Insecurity Scale. Categorical variables were analyzed using the chi-square test followed by multiple logistic regression for the association analysis, and their magnitude was estimated by the crude and adjusted odds ratio (OR). The prevalence of FI found in the sample was 13.6% and the factors associated with it were: per capita family income less than half the minimum wage, self-declared black skin color and presence of depressive symptoms. In addition to this result, it was observed that FI increases the chances of shorter telomere length regardless of sex, age group, skin color, consumption of milk and dairy products, living arrangement, difficulty in carrying out basic activities of daily living, regular physical activity and smoking. Such findings highlight the importance of ensuring full access to adequate nutrition for this population, aiming for healthier aging.